Mucosal-Associated Invariant T Cell Features and TCR Repertoire Characteristics During the Course of Multiple Sclerosis - Carnero Contentti, Edgar; Farez, Mauricio F.; Correale, Jorge (Frontiers in Immunology, 2019)
Objective: To investigate the frequency, phenotype, function and longitudinal repertoire of Mucosal-associated invariant T (MAIT) cells in relapsing remitting (RRMS) and primary progressive MS (PPMS) patients Methods: Forty-five RRMS patients in remission, 20 RRMS patients experiencing exacerbations, 15 PPMS patients and 30 healthy controls (HCs) were included in the study. MAIT cells were identified phenotypically as CD3+ TCRγδ− Vα7.2 + CD161high. In 15 patients, MAIT cell number and MRI lesions were evaluated every 6 months, during 36 months. MAIT cell TCRVβ repertoire was defined using single cell cloning and mRNA sequencing. Results: Circulating MAIT cells were significantly reduced in both RRMS and PPMS patients, particularly during exacerbations, compared to healthy subjects. This decrease was accompanied by pro-inflammatory cytokine production (TNF-α, IFN-γ, IL-17 and GM-CSF). MAIT cells numbers were also lower during MS relapses. Three months post exacerbation, MAIT cell percentages increased significantly along with clinical recovery. Likewise, we observed inverse correlation between MRI lesions and MAIT cell numbers. In paired samples, MAIT cell percentage was significantly higher in CSF than peripheral blood. Finally, MAIT cells showed limited TCRVβ repertoires, in both CSF and peripheral blood, which remained stable over time. Conclusions: MAIT cell levels correlated with MS course both clinically and radiologically, showing marked and sustained oligoclonality. These findings may contribute to a better understanding of pathophysiological phenomena underlying the course of MS, and discovery of MAIT cell inhibitors could pave the way for the development of new therapeutic strategies.